Output Decline and Government Expenditures in European Transition Economies - Schwartz, Gerd (IMF Working Papers; Working Paper ;, 1994)
This paper discusses the role of government expenditure policies in the decline in aggregate output in European transition economies. It is argued that there is little evidence for the hypothesis that more expansionary expenditure policies would have helped to mitigate the output decline. While measurement problems allow for very preliminary conclusions, it appears that government expenditures were, generally, not a binding constraint for output. In those cases where it could be argued that government expenditures were a binding constraint, they were usually not the only one. Government expenditure levels still remain on the high side, at least when compared with European market-based economies, and there exists few reasons for pursuing expansionary expenditure policies to lift European transition economies out of the 'transitional recession.' While raising expenditure levels per se is an unappealing policy choice, a further reordering of expenditure priorities is desirable. In particular, increases in the share of government expenditures on capital--human and physical--are needed to improve long-run output potential.